Aplicación kinesioterapeutica para fortalecimiento muscular isquiotibial en pacientes con prótesis de cadera total de 40 a 70 años de edad que acuden al área de fisioterapia del Hospital General Riobamba-IESS, 2017-2018 - Arias Orellana, María Gabriela (2018)
The principal reason to a person present a total hip prosthesis is the presence of an osteoarthritis in its most chronic phase caused by a deterioration of the joint itself, where its most frequent symptomatology is pain and functional impotence, as well as joint stiffness For this reason, it was taken into account for the realization of this research work the application of kinesiotherapeutics for hamstring muscle strengthening in patients with total hip prosthesis because it has a high efficacy index, especially in patients who come to the Physiotherapy area of the Riobamba IESS General Hospital. The research project in the theoretical framework contains a specific summary of the different bibliographical sources found in the exposed subject, the methodological framework will consist of several methods used for research such as: Hypothetical-deductive, field and experimental in which techniques were used as initial and final physiotherapeutic assessment sheets, where its structure includes the pain test, muscle test and goniometric test, which showed that 70% of the patients attended improved their joint range, therefore, the activities of the daily life improved considerably.